2014
DOI: 10.1097/bpo.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Patient Outcomes in the Operative and Nonoperative Management of High-Grade Spondylolisthesis in Children

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 12 publications
0
17
0
2
Order By: Relevance
“…Finally, 5 eligible studies were identified, consisting of 1 observational case series, 10 1 prospective database, 13 and 3 retrospective cohort studies. 6 , 11 , 12 Table 1 provides a summary of characteristics of these studies, including author, year of publication, nation, and study design, number of patients, follow-up time, operative or nonoperative intervention, and clinical outcome. Of the 5 articles selected for inclusion, 3 studies measured the outcome of the treatment on the HRQOL (questionnaire) and 2 studies measured radiographic evidence of progression of slip.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 5 eligible studies were identified, consisting of 1 observational case series, 10 1 prospective database, 13 and 3 retrospective cohort studies. 6 , 11 , 12 Table 1 provides a summary of characteristics of these studies, including author, year of publication, nation, and study design, number of patients, follow-up time, operative or nonoperative intervention, and clinical outcome. Of the 5 articles selected for inclusion, 3 studies measured the outcome of the treatment on the HRQOL (questionnaire) and 2 studies measured radiographic evidence of progression of slip.…”
Section: Resultsmentioning
confidence: 99%
“…The studies showed in general problems with follow-up and missing data for each variable of interest. The quality of the studies was in general considered low 10 or moderate 6 , 11 , 13 ranging from 5 to 7 points according to the NOS-scale (see Table 2 ). One study was judged as a high-quality study with 8 points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Так, Lundine et al [42] свидетельствуют об отсутствии различий в жалобах и качестве жизни у пациентов, перенесших операцию по поводу спондилолистеза, и у детей и подростков, получавших консервативную терапию. При этом риск неблагоприятного результата выше при исходно более высокой степени спондилолистеза в обеих группах.…”
Section: сочетанные патологииunclassified
“…Хирургическое лечение спондилолистезов высокой степени в настоящее время представляет собой актуальную проблему. Не разработан алгоритм выбора метода хирургического лечения пациентов с данной патологией, остаются дискуссионными способы хирургического лечения, исполь зование редукционных маневров, отсутствуют исследования высокой степени достоверности [22,26,27]. Описаны несколько способов хирургического лечения спондилолистезов высокой степени: задний спондилодез аутокостью in situ (техника Wiltse), инструментальная фиксация in situ с задним спондилодезом аутокостью, корригирующий межтеловой спондилодез (по Dubousset) [28], редукция позвонка с межтеловым спондилодезом, в том числе вышележащего сегмента с транспедикулярной фиксацией, транссакральная винтовая фиксация in situ [29,30].…”
Section: Introductionunclassified